Strengthening coastal resilience through community-based mangrove conservation - Putra, Dinda Syufradian; Yusuf, Muhammad; Hapsa, Hapsa; Rizal, Azira Novia; Al Kausar, Jefri; Rahmadani, Suci; Maielayuskha, Maielayuskha (Community Empowerment, 2025)
Mangrove ecosystem degradation due to land conversion and climate change threatens coastal resilience and community livelihoods in Kuala Simbur Village, Jambi. This community service program aims to enhance ecological awareness and strengthen institutional collaboration in mangrove conservation. Utilizing a participatory approach, the program engaged the village government, Village Consultative Body (BPD), and local community groups through environmental regulation education, participatory problem identification, and conservation action planning. Results indicated a significant increase in public understanding of environmental risks and the ecological functions of mangroves. The program's tangible impacts include the formation of community-based mangrove conservation groups and the strengthening of village regulatory frameworks for sustainable coastal management. Community participation increased in direct actions such as conservation area monitoring and land rehabilitation. This initiative demonstrates that the synergy between community awareness and village institutional support is a decisive factor in the successful preservation of blue carbon ecosystems in coastal regions.